Developing Interactive E-Book for Early Reading-Writing Stage at Class I Elementary School: Pengembangan E-Book Interaktif Membaca Menulis Permulaan di Kelas I Sekolah Dasar - Janawati , Desak Putu Anom; Pradnyana, Putu Beny; Darmayanti, N.W.S.; Sudirman, S.Pd., M. Pd., I Nyoman (Pedagogia : Jurnal Pendidikan, 2022)
The interactive e-book was developed to improve early reading and writing skills as log of pandemic Covid-19. The type of this research is R&D with the product of this research is the E-Book Interactive reading and writing starters. The questionnaire instrument was used as a research data collection technique. The results of the product validity test show the following results. First, the appearance of the interactive E- book product has an attractive appearance, second, the selection of an attractive typeface and the presentation of animated text in the form of a video embedded in the interactive E-book. Third, to get students involved in learning activities it is necessary to have interaction in learning, interesting content and presentations combbined with learning videos to explain the material interactively